When God made light - Turner, Matthew Paul, 1973- (Waterbrook, 2018)
'Let there be light!' that's what God said. And light began shining and then started to spread." Wild and creative illustrations from top children's illustrator David Catrow pair with Matthew Paul Turner's lyrical verse in this message of a God-made light that cuts through darkness to bring vision and hope to all young readers.